Inspeksi Sanitasi Lingkungan Sekolah Di SMA Negeri 1 Martapura - Hendra Hendra; Darmiah Darmiah; Imam Santoso; Erminawati Erminawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: The Sanitation Inspection in SMA Negeri 1 Martapura. Public places have potential as a place of transmission of disease, pollution, or other health problems. Places or public service facilities that are obliged to carry out environmental sanitation include public places are managed commercially or public services that have a high intensity of number and time of visit, one of which is the school environment. The study aimed to find out the picture of school environmental sanitation in SMA Negeri 1 Martapura with research variables; Cleanliness and neatness of building space, condition of toilet, building construction, and environmental coaching. Research method’s observational, and measurement of environmental quality (lighting and noise). Processing and data analysis done descriptively. The result of measurement of building cleanliness variables obtained value of 140 points (70%), toilet condition variable 585 points (73.12%), building construction variables 575 (95,83%) and environmental coaching 2,060 points (85,83% ). Overall assessment of school environmental santitasi obtained points 3,360 points (84%) so that included in the category of healthy schools. It is recommended that schools at WC/KM at schools equip with lights for lighting in WC/KM to be bright, sewage discharges with closed construction, students better maintain cleanliness and tidiness of classes, curtains when learning activities are opened, and more activate the activities of clean Friday. Keywords: Inspection; Sanitation; School Environment.